Le coordonnant en tant qu’outil de cohérence du texte : implications traductologiques - Bulikowski, Brunon (Studia Romanica Posnaniensia, 2009)
Co-ordinate connector as a tool for text coherence. The article shows the role of language mechanisms in respect of the co-ordination relation in the process of text coherence. The author considers the range of the phenomena studied and indicates that they go well beyond the boundaries of a complex sentence. Simultaneously, he shows their role in ensuring the isotopy of a text. In another place in the article, the author focuses his attention on the function of a co-ordinate conjunction at the inter-sentence level and, at the same time, shows the location of the phenomenon in the process of translation.